BPM Governance in Industry 4.0: The Dynamic BPM Approach - Marek SZELAGOWSKI; Justyna BERNIAK-WOZNY; Michał TUZ (Communications of International Proceedings, 2021)
The purpose of this article is to discuss the need to change the BPM Governance (BPMG) rules as a result of the diversification of the nature of business processes in Industry 4.0. The traditional approach to business processes assumes control of the flow of well-structured activities that the organisation carries out to achieve its goals, and managing them, focused on their improvement through increased efficiency. However, in Industry 4.0, it is necessary to take into account the management of unstructured processes. This task is all the more important as these processes are of decisive importance for the competitive position of the company, and the management of knowledge created as part of the process implementation becomes an end in itself - as important as the management of effectiveness. The paper is conceptual in nature and is grounded in the theories of Business Process Management (BPM), Business Process Management Governance (BPMG) and Dynamic BPM. The article presents the necessity and directions of necessary changes in BPMG, from the perspective of the dynamic BPM approach. It also presents proposals for the changes to the BPM Lifecycle and the Deming-Shewhart Cycle extension, and the resulting implications for BPMG.
Keywords: Business Process Management (BPM); Business Process Management Governance (BPMG); Dynamic BPM; Industry 4.0.